Studying the personality profile of drug addicts by utilizing two models of Cloninger and Eysneck (Drug Control Headquarters, Research and Education Office, 2008)
Objectives: Identifying personality factors of tendency to drugs can be helpful in better recognition and treatment of drug-dependency and also by providing consulting and psychological services can relatively prevents from vulnerable people to be addicted. This research therefore aims to investigate personality profile of substance dependent by using personality models of Cloninger and Eysenck. Methods: 100 substance-dependent and 100 normal men selected by available sampling method and completed Temperament and Character Inventory of Cloninger (TCI) and Eysenck Personality Questionnaire _ Revised (EPQ-R). Also, some democratic information regarding substance- dependents collected. Research data were analyzed by inferential and descriptive statistics. Findings: This research showed that there are significant differences in temperament dimensions of novelty seeking and harm avoidance and character dimensions of self-direction and cooperativeness of Cloninger model and neuroticism and psychosis dimensions of Eysenck model between substance- dependent men and normal men. Results: Comparing in normal men, substance dependent men gained higher scores at novelty seeking and neuroticism and psychosis, and lower scores at self-direction and cooperativeness.